2013
DOI: 10.1016/j.drugalcdep.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable effect of acute varenicline on tonic versus cue-provoked craving in non-treatment-motivated heavy smokers

Abstract: Rationale The effectiveness of varenicline for smoking cessation has been established, but little is known about the psychological processes that mediate this clinical outcome. Objectives This study evaluated the effect of a single dose of varenicline on tonic and cue-provoked changes in craving, withdrawal, and affect using a randomized, double-blind, placebo-controlled, cross-over design. Methods Following overnight abstinence, 38 non-treatment-motivated smokers received either varenicline 2 mg or matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
4
20
1
Order By: Relevance
“…5 Individual variables related Hitsman et al, 2013;Shiffman & Ferguson, 2008), very few studies have explored which variables are associated with craving reductions. Those studies have mainly explored the influence of gender (Collins, Nair, & Komaroff, 2011;Unrod et al, 2013), nicotine dependence (Canterberry et al, 2013;Kober et al, 2010;Li et al, 2013) and…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…5 Individual variables related Hitsman et al, 2013;Shiffman & Ferguson, 2008), very few studies have explored which variables are associated with craving reductions. Those studies have mainly explored the influence of gender (Collins, Nair, & Komaroff, 2011;Unrod et al, 2013), nicotine dependence (Canterberry et al, 2013;Kober et al, 2010;Li et al, 2013) and…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Varenicline is an established treatment for NUD (Hartmann-Boyce et al, 2014), and its efficacy is likely mediated, in part, by reductions in craving (Ashare et al, 2012; Hajek et al, 2011; Hitsman et al, 2013), although this has not been observed in all studies of varenicline (Jhanjee et al, 2015). Investigations into the effects of varenicline on withdrawal have been even more mixed with some showing improvements in withdrawal (Hitsman et al, 2013) and others not (Brandon et al, 2011; Jhanjee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into the effects of varenicline on withdrawal have been even more mixed with some showing improvements in withdrawal (Hitsman et al, 2013) and others not (Brandon et al, 2011; Jhanjee et al, 2015). Finally, there is some evidence to suggest that varenicline may be acting via improvements in inhibitory control and attention (and thus impulsiveness) as well (Austin et al, 2014; Rhodes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The present report is part of a study, evaluating the effect of varenicline on ameliorating abstinence-and cue-induced nicotine craving and withdrawal symptoms in a population of 40 smokers not currently intending to quit. 14 The cue-reactivity model was based on a rigorous laboratory-based assessment paradigm including in vivo exposure to smoking cues, specifically designed to provoke craving and assess the effects of smoking cues on the urge to smoke and withdrawal symptoms. Results showed that a single dose of varenicline reduced tonic craving levels in smokers who refrained from smoking, but not cue-provoked craving.…”
Section: Introductionmentioning
confidence: 99%